Critical amino acids in the TM2 of EAAT2 are essential for membrane‐bound localization, substrate binding, transporter function and anion currents. Issue 5 (1st February 2021) - Mai, Dongmei; Chen, Rongqing; Wang, Ji; Zheng, Jiawei; Zhang, Xiuping; Qu, Shaogang
Abstract: Excitatory amino acid transporter 2 (EAAT2), the gene of which is known as solute carrier family 1 member 2 ( SLC1A2 ), is an important membrane‐bound transporter that mediates approximately 90% of the transport and clearance of l ‐glutamate at synapses in the central nervous system (CNS). Transmembrane domain 2 (TM2) of EAAT2 is close to hairpin loop 2 (HP2) and far away from HP1 in the inward‐facing conformation. In the present study, 14 crucial amino acid residues of TM2 were identified via alanine‐scanning mutations. Further analysis in EAAT2‐transfected HeLa cells in vitro showed that alanine substitutions of these residues resulted in a decrease in the efficiency of trafficking/targeting to the plasma membrane and/or reduced functionality of membrane‐bound, which resulted in impaired transporter activity. After additional mutations, the transporter activities of some alanine‐substitution mutants recovered. Specifically, the P95A mutant decreased EAAT2‐associated anion currents. The Michaelis constant (Km ) values of the mutant proteins L85A, L92A and L101A were increased significantly, whereas R87 and P95A were decreased significantly, indicating that the mutations L85A, L92A and L101A reduced the affinity of the transporter and the substrate, whereas R87A and P95A enhanced this affinity. The maximum velocity (Vmax) values of all 14 alanine mutant proteins were decreased significantly, indicating that all these mutations reduced the substrate transport rate. These results suggest that critical residues in TM2 affect not only the protein expression and membrane‐bound localization of EAAT2, but also its interactions with substrates. Additionally, our findings elucidate that the P95A mutant decreased EAAT2‐related anion currents. Our results indicate that the TM2 of EAAT2 plays a vital role in the transport process. The key residues in TM2 affect protein expression in the membrane, substrate transport and the anion currents of EAAT2.